Integrating cover crops in high tunnel production systems - Skinner, Ashlee Georgetta (Kansas State University, 2020)
The use of high tunnel systems for vegetable crop production is increasing throughout the Central United States. High tunnels provide environmental protection, season extension, increased crop quality and yield, and pest and disease exclusion. In contrast to greenhouse production, high tunnel production is typically soil-based. Intensive cultivation and/or reduced crop rotation intervals that occur in high tunnels and can lead to degradation of soil health. Therefore, this study identified were to identify summer and winter cover crop species could be viable for high tunnel systems and determine their impact on soil properties and arthropod abundance. High tunnel experiments were conducted in 2018 and 2019. There were eight cover crop treatments planted in each season, which included grass, cereal, and legume combinations as well as a weed-free control. Hairy vetch (Vicia villosa) and cowpea (Vigna unguiculata) were the legume crops planted in the winter and summer experiments, respectively. In the winter experiments, cereal rye (Secale cereal) and hairy vetch treatment resulted in the highest biomass yields and cover crop nitrogen contribution (P <0.05). In the summer experiment, summer cover crop available N (lbs/acre) was highest for the sorghum-sudangrass treatment (Sorghum x drummondi) averaging 100 lbs/acre (P <0.05) in both years. Increases in soil total carbon (STC), organic matter (OM), and soil total nitrogen (STN) indicated positive effects of cover cropping on soil properties in both seasons. Finally, mites were the dominant soil arthropods recovered in the study and an increase in soil total carbon resulted in higher mite numbers in the summer experiment. Soil organic matter influenced the abundance of mites differently in the two seasons. In the summer experiment, an increase in percent organic matter after termination was associated with an increase in mite abundance. However, in the winter experiment, higher organic matter was associated with lower mite numbers. In the summer experiment, mite abundance was higher in buckwheat and cowpea cover crop treatments than the other treatments. A mean of 0.82 mites per 96 g of soil were recovered in 2018 and 2019 from the buckwheat and cowpea treatment, whereas in the control treatment an average of 0.02 mites were recovered in the summer experiments. Soil moisture and soil total nitrogen did not have an effect on mite abundance in the study. Therefore, in this study cover crop rotations in high tunnels unveiled associated trends in soil properties and arthropod abundance.
Keywords: High tunnels; Cover crops